Integrated design and fabrication strategies based on bioprinting for skeletal muscle regeneration: Current status and future perspectives. (January 2023) - Ma, Hong; Xing, Fei; Yu, Peiyun; Xu, Jiawei; Wu, Xinyu; Luo, Rong; Xiang, Zhou; Maria Rommens, Pol; Duan, Xin; Ritz, Ulrike
Graphical abstract: Highlights: Integrated design and fabrication strategies based on bioprinting for skeletal muscle regeneration are reviewed. The bioinks and bioprinting methods used for skeletal muscle regeneration are summarized. Delivery of seed cells and growth factors based on bioprinting for skeletal muscle regeneration are overviewed. The challenge and future perspectives towards bioprinting in skeletal muscle regeneration are prospected. Abstract: The number of skeletal muscle injuries derived from myopathies, exercise, and trauma, is growing due to increasing sports activities in normal life of people. Skeletal muscle has a robust capacity for regeneration following injury. However, few if any effective therapeutic options for volumetric muscle loss are available. Poor repair of muscle injury will lead to skeletal muscle dysfunction, resulting in physical pain and even seriously compromising daily life. As a new technology of biomedicine, 3D bioprinting is widely used in the field of tissue engineering and regenerative medicine due to its enormous advantages. 3D bioprinting creates biological structures similar to that of protists by precisely constructing a specified geometric shape at micro/nano levels, thus addressing the unmet needs in tissue replacement and organ transplantation. With the further application of bioprinting in various tissue repairs, more and more researchers utilized 3D bioprinting in skeletal muscle regeneration. Various bioinks, such as alginate, gelatin, fibrin hydrogels, and extracellular matrix (ECM), loaded with functional seed cells or growth factors have been applied to fabricating 3D bioprinted constructs with complicated inner structures for skeletal muscle regeneration. Therefore, we conducted this review to report the skeletal muscle regeneration process, the development status of bioprinting technology, and the mechanism of promoting skeletal muscle repair. In addition, the current challenges and further perspectives of skeletal muscle regeneration by bioprinting are also discussed in this study.